Implementasi Prinsip Mu’asyarah bil Ma’ruf dalam Resolusi Konflik Pasangan Berpendidikan Agama: Studi di Kelurahan Situ Gede Bogor Barat Kota Bogor - Muchlish Baihaqi; Fachri Fachruddin; Muhammad Hidayat (Lembaga Yasin AlSys, 2026)
Although mu’āsyarah bi al-ma‘rūf has been widely discussed as an ethical principle in marital relationships, studies examining its application to conflict resolution among couples with a religious education remain limited. This study aims to analyze how couples with a religious education understand the principle of mu’āsyarah bi al-ma‘rūf, identify the dynamics of family conflict, and explore the application of this principle to conflict resolution. This study employed a qualitative approach with a field-study design in Situ Gede Urban Village. Data were collected through interviews with newly married and long-married couples, prospective brides and grooms, marriage registrars, officers of the Marriage Advisory, Development, and Preservation Agency (BP4), and religious leaders and were subsequently analyzed descriptively according to the research themes. The findings indicate that mu’āsyarah bi al-ma‘rūf is understood as the principle of treating one’s spouse with gentleness, attentiveness, respect, affection, acceptance of shortcomings, and fulfillment of rights and obligations. Family conflicts were primarily triggered by differences in character, habits, mindsets, and egos; communication and financial problems; long-distance relationships; and interference from extended family members. This principle was applied through emotional and ego control, self-reflection, acceptance of one’s spouse, open communication, dialogue, deliberation, clarification, and the involvement of family members, religious leaders, the Office of Religious Affairs (KUA), or BP4 when necessary. Religious values serve as a normative and spiritual foundation for guiding conflict resolution. However, religious education only provides a foundation for understanding and does not automatically guarantee couples’ ability to practice mu’āsyarah bi al-ma‘rūf in emotionally charged situations. These findings underscore the importance of integrating religious understanding, self-control, and constructive communication into family conflict resolution and have implications for strengthening premarital education and religious values-based family development programs.